The Effect of Probiotic in Milk Fermentation Towards Decreasing Cholesterol Levels: in Vivo Studies - Ria Dewi Andriani; Premy Puspitawati Rahayu; Mulia Winirsya Apriliyani (Faculty of Animal Science Universitas Brawijaya, 2020)
Hypercholesterolemia is a disease that is indicated by the increasing level of cholesterol in the body and also as one of the factors causing cardiovascular disease. An alternative that can be done to prevent hypercholesterolemia is by consuming fermented milk. Skim milk is fermented using probiotic of Lactobacillus acidophillus, Lactobacillus plantarum and Streptococcus thermophilus. The skimmed milk that has been fermented is then tested for total lactic acid bacteria, total acid, pH, and in vivo analysis for antihypercholesterolemia activity using animal model. In this study, the animal models used were male white rats which were grouped into three treatment groups, namely negative control, positive control, and fermented milk group. The result of the study shows that the total lactic acid bacteria, total acid and pH of fermented skim milk were 5.25 x109 CFU/ml; 2.190% and pH 4.06, respectively. From the results, fermented milk with probiotics has the ability to reduce cholesterol levels in the blood of male white rats effectively in vivo.